2007
DOI: 10.1002/jsfa.2911
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to aerobic deterioration of total mixed ration silage inoculated with and without homofermentative or heterofermentative lactic acid bacteria

Abstract: Wet brewers grains were stored as a total mixed ration (TMR) in laboratory silos with lucerne hay, cracked maize, sugar beet pulp, soya bean meal and molasses at 5:1:1:1:1:1 on fresh weight basis. The TMR mixture was inoculated with or without Lactobacillus casei or Lactobacillus buchneri to obtain silages with differing fermentation and stability after exposure to air. In the first experiment, ensiling was stopped at 10, 20 and 60 days, and the stability was tested for the following 7 days. Ethanol and lactic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
2
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 13 publications
0
14
2
1
Order By: Relevance
“…Although this property was demonstrated in both BGT and SCT silages (Wang & Nishino 2008a), yeasts were found at 10 4 cfu g −1 level in SCT 0 silage in this study. Also, although we reported that yeasts remained undetectable for 7 days when BGT silage was exposed to air (Nishino & Hattori 2007; Wang & Nishino 2008b), BGT 7 silage contained 10 3 cfu g −1 of yeasts in this study. Because previous experiments were conducted using vacuum packed pouch silos, the stability of TMR silage might be less notified when stored in bag silos.…”
Section: Resultscontrasting
confidence: 65%
See 3 more Smart Citations
“…Although this property was demonstrated in both BGT and SCT silages (Wang & Nishino 2008a), yeasts were found at 10 4 cfu g −1 level in SCT 0 silage in this study. Also, although we reported that yeasts remained undetectable for 7 days when BGT silage was exposed to air (Nishino & Hattori 2007; Wang & Nishino 2008b), BGT 7 silage contained 10 3 cfu g −1 of yeasts in this study. Because previous experiments were conducted using vacuum packed pouch silos, the stability of TMR silage might be less notified when stored in bag silos.…”
Section: Resultscontrasting
confidence: 65%
“…It has been shown that yeasts would decrease to below detectable levels (10 2 cfu g −1 ) when TMR silage is stored for approximately 2 months (Nishino et al . 2004; Nishino & Hattori 2007; Wang & Nishino 2008b). Although this property was demonstrated in both BGT and SCT silages (Wang & Nishino 2008a), yeasts were found at 10 4 cfu g −1 level in SCT 0 silage in this study.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, its low digestibility and protein content limit its use as feed for ruminants. It is fortunate that some researchers have found that some agricultural by‐products could be incorporated into rations by ensiling (Cao, Cai, Hirakubo, Fukui, & Matsuyama, ; Cao, Cai, Takahashi, et al., ; Nishino & Hattori, ). If straws could substitute a part of forage and are conserved well as mixed silage, it would enlarge the feed resource and alleviate the shortage of feedstuffs.…”
Section: Introductionmentioning
confidence: 99%